2018
DOI: 10.3855/jidc.10980
|View full text |Cite
|
Sign up to set email alerts
|

The presence of periopathogenic bacteria in subgingival and atherosclerotic plaques – An age related comparative analysis

Abstract: Introduction: There is a known connection between periodontitis and atherosclerosis and the presence of periopathogens in blood vessels. However, changes of the oral microflora related to the aging process and its possible effects on atherosclerosis, have yet to be analyzed. The aim of this study was to assess temporal changes in the frequency of periodontal bacteria in the subgingival plaque and in atherosclerotic blood vessels of patients with atherosclerosis. Methodology:The study included 100 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…These results are in accordance with many published studies on this topic [20][21][22][23][24][25][26][27][28][29][30][31]. The data of this study were consistent with those reported by Haraszthy et al [20] (26% for P.g., 18% for A.a., 30% positive for T.f., and 14% for P.i.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with many published studies on this topic [20][21][22][23][24][25][26][27][28][29][30][31]. The data of this study were consistent with those reported by Haraszthy et al [20] (26% for P.g., 18% for A.a., 30% positive for T.f., and 14% for P.i.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, DNA molecules of Treponema denticola was detected in (45/100) 45% of cardiovascular atheromatous plaque samples, this result was in accordance with the previous correlated studies that reported presence of DNA samples of T. denticola in (49.01 %) of atherosclerotic plaques & (39.21%) in both sub gingival & coronary atheromatous plaque samples (21) as well as, the proportion of T. denticola DNA samples in the current study was greater than the ratios of other corresponding studies that revealed DNA samples of T. denticola were (6%) & (23.1% ) in atherosclerotic samples (30,22) respectively, & less than in other related studies which mentioned the ratios of T. denticola DNA samples in sub gingival plaques & atheromatous plaque lesions was (54.5%) (31,21) . Indeed, Mahendra et al reported presence of periodontal bacteria in Coronary Heart Disease patients & T. denticola was meaningfully improved from 4 1 .…”
Section: Resultscontrasting
confidence: 69%
“…Otherwise, these finding may be due to the greater number of the males (63) in comparison to the number of the females (37) in the current study (63)(64) . Furthermore, positive atherosclerotic plaques with T. denticola DNA samples were present in elderly patients above 50 years old 23/45(51%) approximate to 22/45(49%) in atherosclerotic vessels patients younger than 50 years old with no significant importance, table (3), these finding may be due to decrease the activity of immune system (adaptive immune response to bacterial infections) in affected participants which was in line with closely related study referred that oldness moderate adaptive immune response , in excess of innate immune response , reduction in immune system will rise susceptibility & occurrence to contagions (30,37) . These results may unpredictable thru the results of Janket & colleagues (38) , Mattila & colleagues (39) that suggested the periodontal disease might generate a greater risk for CVD between younger contributors.…”
Section: Resultssupporting
confidence: 69%
“…Periodontitis has effects on the endothelial function, causing endothelial dysfunction, stiffness of the arteries and high BP [ 98 ], and hypertension-associated oral pathogens (HOP) as C. rectus , V. parvula , P. melaninogenica have been identified [ 99 ]. Late colonizers as P. gingivalis , A. actinomycetemconcomitan , T. forsythia, and T. denticola have been explored in vascular atherosclerosis lesions but their possible association with blood pressure has not been evaluated [ 100 , 101 ]. Hypertension, such as periodontitis, is considered a low-grade inflammatory disorder and it is marked by the presence of pro-inflammatory cytokines [ 102 ].…”
Section: Periodontitis Affects Hypertension (Ht)mentioning
confidence: 99%